Kepemimpinan Visioner dan Corporate Culture dalam Meningkatkan Daya Saing dan Minat Pelanggan Pendidikan Islam Transformatif - Maksum, Ali; Eko Sujianto, Agus; Sulistyorini (Kartika: Jurnal Studi Keislaman, 2026)
In today's increasingly competitive era, Islamic education faces significant challenges in maintaining its relevance and enhancing its competitiveness. Many Islamic educational institutions struggle to attract public interest, both in terms of academic quality and institutional management. One potential solution lies in visionary leadership combined with a strong corporate culture. Visionary leadership not only sets the institution’s direction and goals but also fosters innovation and strategies that adapt to changing times. Meanwhile, a robust corporate culture establishes a solid institutional identity, strengthens loyalty, and creates a conducive environment for educational growth and development. This study employs the library research method by analyzing various relevant literatures to understand the relationship between these concepts in the context of transformative Islamic education. The findings indicate that the synergy between visionary leadership and corporate culture enhances institutional competitiveness, broadens its appeal to the public, and ensures sustainability amid globalization. The study’s implications emphasize the need for managerial reform in Islamic educational institutions to remain relevant, innovative, and highly competitive in the digital era